2020
DOI: 10.1177/0731684420931589
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of heat generation using a microscopic cutting model with thermo-mechanical coupling for carbon fiber reinforced polymer composites

Abstract: A three-dimensional micromechanical finite element cutting model with the thermo-mechanical coupling was developed for carbon fiber reinforced polymer composites in the paper. The finite element modeling considers the three phases of a composite, in which the interphase between the fiber and matrix can realize heat transfer and allow debonding to represent the failure of composites. The model predictions of the machining responses, such as cutting temperature and subsurface damage, at different fiber orientati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…FRP machining e.g., [9][10][11][12]14,15,[32][33][34][35]. However, significant deficiencies in thermomechanical modeling of new hybrid composites still exist.…”
Section: Heat Dissipatedmentioning
confidence: 99%
“…FRP machining e.g., [9][10][11][12]14,15,[32][33][34][35]. However, significant deficiencies in thermomechanical modeling of new hybrid composites still exist.…”
Section: Heat Dissipatedmentioning
confidence: 99%
“…The resin surface temperature is higher because the thermal conductivity of the resin is low. Sheikh-Ahmad et al [94] proposed that inverse heat conduction method was an effective and efficient technique for determining the energy balance in machining CFRP. Qian et al [95] found that the heat generation mechanism at 90° was more complex compared with 0°, resulting in the highest cutting temperature when the FCA was 90°.…”
Section: Thermal and Mechanical Behaviormentioning
confidence: 99%
“…[19][20][21] To examine the detail information of subsurface damage, various experimental observation technologies have been used, such as the application of the X-ray tomography, optical and electron microscopy techniques. [22][23][24][25] On the other hand, as the development of modeling tools, prediction of machining-induced damage in composite cutting has been commonly achieved using finite element method (FEM). Wang et al 26 studied the influences of machining parameters on surface subsurface damage by using the finite element modeling in CFRP cutting.…”
Section: Introductionmentioning
confidence: 99%
“…19-21 To examine the detail information of subsurface damage, various experimental observation technologies have been used, such as the application of the X-ray tomography, optical and electron microscopy techniques. 22-25…”
Section: Introductionmentioning
confidence: 99%